Handbook of research on computer-enhanced language acquisition and learning - Zhang; Barber (Information Science Reference, 2008)
"This book provides comprehensive coverage of successful translation of language learning designs utilizing ICT in practical learning contexts. It offers researchers, scholars, students, and professionals worldwide, access to the latest knowledge related to research on computer-enhanced language acquisition and learning"--Provided by publisher